ANALISA KONTEN NILAI-NILAI MODERASI ISLAM DALAM BUKU AJAR AKIDAH AKHLAK DI MADRASAH ALIYAH SEBAGAI UPAYA PENCEGAHAN RADIKALISASI - Febrianti, Fia Salsa; Fuad, Ai Fatimah Nur; Basyirah, Rafa; Iryanti, Shobah Shofariyani (Journal of Research and Thought on Islamic Education (JRTIE), 2023)
Radicalization or the process of bringing the influence of radical ideology into a person's views and attitudes, is vulnerable to school students. However, it is still rare to find research that specifically discusses the influence of textbooks in preventing the entry of radical influences into school students. Therefore, this research aims to analyze the Akidah Akhlak text book used in Senior High School. This qualitative research is based on library-based research using analytical methods that focus on content analysis. The results of the research concluded that in the Akidah Akhlak text book, the values of Islamic moderation are found in various forms such as in images, discourses or stories, and texts. The existence of Islamic moderation values in the Class XII Aqidah Akhlak text book at Madrasah Aliyah has two contributions to the process of education emong students. First, it can strengthen students' moderate views and attitudes, including having a fair/balanced/equal attitude, a tolerant attitude, a nationalistic attitude and accommodating towards lokal culture. Second, it can prevent students from being influenced by radicalism, intolerance, extremism and violence in the name of religion. This research should be continously developed in relation to many aspects of education for preventing radicalisation among students.